A National Analysis of Pediatric Trauma Care Utilization and Outcomes in the United States. Issue 1 (January 2019) - Myers, Sage R.; Branas, Charles C.; French, Benjamin; Nance, Michael L.; Carr, Brendan G.
Abstract : Objectives: More childhood deaths are attributed to trauma than all other causes combined. Our objectives were to provide the first national description of the proportion of injured children treated at pediatric trauma centers (TCs), and to provide clarity to the presumed benefit of pediatric TC verification by comparing injury mortality across hospital types. Methods: We performed a population-based cohort study using the 2006 Healthcare Cost and Utilization Project Kids Inpatient Database combined with national TC inventories. We included pediatric discharges (⩽16 y) with the International Classification of Diseases, Ninth Revision code(s) for injury. Descriptive analyses were performed evaluating proportions of injured children cared for by TC level. Multivariable logistic regression models were used to estimate differences in in-hospital mortality by TC type (among level-1 TCs only). Analyses were survey-weighted using Healthcare Cost and Utilization Project sampling weights. Results: Of 153, 380 injured children, 22.3% were admitted to pediatric TCs, 45.2% to general TCs, and 32.6% to non-TCs. Overall mortality was 0.9%. Among level-1 TCs, raw mortality was 1.0% pediatric TC, 1.4% dual TC, and 2.1% general TC. In adjusted analyses, treatment at level-1 pediatric TCs was associated with a significant mortality decrease compared to level-1 general TCs (adjusted odds ratio, 0.6; 95% confidence intervals, 0.4–0.9). Conclusions: Our results provide the first national evidence that treatment at verified pediatric TCs may improve outcomes, supporting a survival benefit with pediatric trauma verification. Given lack of similar survival advantage found for level-1 dual TCs (both general/pediatric verified), we highlight the need for further investigation to understand factors responsible for the survival advantage at pediatric-only TCs, refine pediatric accreditation guidelines, and disseminate best practices.